Key factors and path selection for enterprise digital transformation: configuration analysis based on fsQCA - Zhou, Yanqiu; Chen, Lei; Zhou, Xu; Hu, Shihua (Frontiers in Sustainability, 2024)
The new digital technology revolution is spurring corporate digital transformation. Presently, the majority of enterprises are still in the digitalization stage. They have yet to pinpoint the key factors and suitable paths for their transformation. Therefore, this study aims to determine which and how factors affect this transformation to improve the current enterprise's digital transformation. We extract key elements affecting corporate digital transformation. Taking 98 representative businesses as examples, we utilize the fuzzy-set qualitative comparative analysis approach (fsQCA) to investigate how different factors combine to achieve digital transformation. The results show that: (1) No single factor can achieve digital transformation for enterprises, as it requires a combination of multiple factors. (2) Four configuration paths can lead to corporate digital transformation. (3) A business can equivalently substitute resource consolidation with strategic planning and human resources to drive digital transformation. This study offers multiple paths for achieving corporate digital transformation to guide businesses in their choice of digital transformation pathways.